Hematopoietic Stem Cell Transplantation for Combined Immunodeficiencies, on Behalf of IEWP-EBMT - Neven, Benedicte; Ferrua, Francesca (Frontiers in Pediatrics, 2020)
Combined immunodeficiencies (CIDs) are a clinically and genetically heterogeneous group of primary immunodeficiencies (PIDs) that affect T-lymphocyte immunity with abnormal development or function. As compared to severe combined immune deficiencies (SCID), these patients are usually diagnosed later. They display a broad infectious susceptibility; immune dysregulation manifestations and chronic lymphoproliferation are also frequent. These complications and their specific treatments can lead to persistent damage to several organs. Prognosis of CIDs is worse as compared to other PIDs. The curative treatment is usually hematopoietic stem cell transplantation (HSCT), but difficult questions remain regarding the definitive indication of HSCT and its timing; the final decision depends on a conjunction of factors such as immunological parameters, severity of clinical manifestations, and natural history of the disease, when molecular diagnosis is known. CD40L deficiency, a CID caused by mutations in CD40LG gene, well illustrates the dilemma between HSCT vs. long-term supportive treatment. This disease leads to higher risk of developing infections from bacterial and intracellular pathogens, especially Pneumocystis and Cryptosporidium spp. While supportive care allows improved survival during childhood, organ damages may develop with increasing age, mainly chronic lung disease and biliary tract disease (secondary to Cryptosporidium spp. infection) that may evolve later to sclerosing cholangitis, a severe complication associated with increased mortality. Early HSCT before organ damage development is associated with best survival and cure rate, while HSCT remains a risky therapeutic option for older patients, for those with organ damage, especially severe liver disease, and/or for those with limited or no donor availability. Prospective studies are needed to analyze risks of HSCT compared to those of life-long supportive therapy, including quality of life measures.